Efﬁcacy of polymyxins in the treatment of carbapenem-resistant Enterobacteriaceae infections: a systematic review and meta-analysis - Ni,Wentao (2015)
In recent years, carbapenem-resistant Enterobacteriaceae has become endemic in many countries. Because of limited treatment options, the abandoned "old antibiotics", polymyxins, have been reintroduced to the clinic. To evaluate the clinical efﬁcacy of polymyxins in the treatment of infections caused by carbapenem-resistant Enterobacteriaceae , we systemically searched the PubMed, Embase, and Cochrane Library databases and analyzed the available evidence. The Preferred Reporting Items for Systematic reviews and Meta-Analysis statement were followed, and the I 2 method was used for heterogeneity. Nineteen controlled and six single-arm cohort studies comprising 1086 patients met the inclusion criteria. For controlled studies, no signiﬁcant difference was noted for overall mortality (OR, 0.79; 95% CI, 0.58-1.08; p = 0.15), clinical response rate (OR, 1.24; 95% CI, 0.61-2.54; p = 0.55), or microbiolog- ical response rate (OR, 0.59; 95% CI, 0.26-1.36; p = 0.22) between polymyxin-treated groups and the control groups. Subgroup analyses showed that 28-day or 30-day mortality was lower in patients who received polymyxin combination therapy than in those who received monotherapy (OR, 0.36; 95% CI, 0.19-0.68; p < 0.01) and the control groups (OR, 0.49; 95% CI, 0.31-0.75; p < 0.01). The results of the six single-arm studies were in accordance with the ﬁndings of controlled studies. One controlled and two single-arm studies that evaluated the occurrence of nephrotoxicity reported a pooled incidence rate of 19.2%. Our results suggest that polymyxins may be as efﬁcacious as other antimicrobial therapies for the treatment of carbapenem-resistant Enterobacteriaceae infection. Compared to polymyxin monotherapy, combination regimens may achieve lower 28-day or 30-day mortality. Future large-volume, well-designed randomized control trials are required to determine the role of polymyxins in treating carbapenem-resistant Enterobacteriaceae infections.